تعزيز الوضوح: تصميم خط رقمي عربي لذوي عسر القراءة - اسماعيل عيسى صالح, زكريا (جامعة بوليتكنك فلسطين, 2026)
هدفت هذه الدراسة إلى تصميم خطّ رقمي عربي ميسّر للقراءة لذوي عسر القراءة، انطلاقًا من مشكلة غياب خطوط عربية متخصصة مبنية على أسس علمية تراعي الخصائص البصرية والبنيوية للخط العربي، مع ندرة الأدوات الموضوعية التي تقيّم مدى ملاءمة الخطوط العربية لهذه الفئة. انطلقت الدراسة من فرضية مؤداها أن تطوير أداة تحليل حاسوبي للخصائص الطباعية العربية يمكن أن يوجّه تصميم خط أكثر وضوحًا، وأن يسهم في تحسين الأداء القرائي لدى المتعلمين ذوي عسر القراءة. تناولت الدراسة في إطارها النظري أربعة محاور رئيسة: الخصائص البنيوية للكتابة العربية ومتطلبات تصميمها الطباعي الرقمي، وعسر القراءة من حيث ماهيته وأبعاده الإدراكية، وتأثير المتغيرات الطباعية في الوضوح القرائي، ثم مراجعة الدراسات السابقة وتحديد الفجوة البحثية في السياق العربي. اعتمدت الدراسة منهجية مختلطة جمعت بين المسار التطويري الحاسوبي والمسار شبه التجريبي. ففي المسار الأول، طُوّرت أداة تحليل حاسوبية باسم "أرابيكليكسيا" لتحويل عدد من المبادئ الإدراكية والطباعية إلى مؤشرات كمية قابلة للقياس. وفي ضوء نتائج هذه الأداة، صُمّم الخط المقترح (ArabicLexia Font) بوصفه خطًا عربيًا وظيفيًا موجّهًا لذوي عسر القراءة. أما في المسار الثاني، فقد جرى التحقق من فاعلية الخط المقترح من خلال تصميم شبه تجريبي شمل عينة مكونة من (21) طالبًا من ذوي عسر القراءة، وُزّعوا على ثلاث مجموعات. وتمثلت أدوات القياس في اختبارات لقياس دقة القراءة، والطلاقة القرائية، وأخطاء الخلط البصري. وأظهرت النتائج تفوق الخط المقترح في مؤشرات الأداء القرائي، إذ حقق متوسط دقة بلغ (90.84%)، مع انخفاض واضح في أخطاء الخلط البصري مقارنة بالمجموعتين الأخريين، في حين سجلت مجموعة التباعد المعدل أدنى مستوى أداء بمتوسط دقة بلغ (62.63%). وتشير هذه النتائج إلى أن تحسين القراءة في العربية لا يتحقق عبر توسيع المسافات وحده، بل عبر هندسة حرفية داخلية أكثر اتساقًا وتمييزًا. وتخلص الدراسة إلى أن تصميم الخط العربي الموجّه لذوي عسر القراءة ينبغي أن يقوم على تحليل بصري-إدراكي دقيق، وأن الأداة المطورة والخط الناتج عنها يقدمان نموذجًا أوليًا يمكن الإفادة منه في تطوير المواد التعليمية والمنصات الرقمية بما يعزز الوضوح القرائي والعدالة البصرية لهذه الفئة. This study aimed to design an Arabic digital typeface that facilitates reading for individuals with dyslexia, in response to the absence of specialized Arabic typefaces grounded in scientific principles that account for the visual and structural characteristics of the Arabic script, as well as the scarcity of objective tools for assessing the suitability of Arabic typefaces for this group. The study was based on the hypothesis that developing a computational tool for analyzing Arabic typographic features could guide the design of a clearer typeface and contribute to improving the reading performance of learners with dyslexia. The theoretical framework of the study addressed four main dimensions: the structural characteristics of Arabic writing and the requirements of its digital typographic design; dyslexia in terms of its nature and cognitive dimensions; the effect of typographic variables on reading clarity; and a review of previous studies with the identification of the research gap in the Arabic context. The study adopted a mixed-methods approach that combined a computational developmental track with a quasi-experimental track. In the first track, a computational analysis tool named ArabicLexia was developed to convert a set of cognitive and typographic principles into measurable quantitative indicators. Based on the outcomes of this tool, the proposed ArabicLexia Font was designed as a functional Arabic typeface intended for individuals with dyslexia. In the second track, the effectiveness of the proposed typeface was examined through a quasi-experimental design involving a sample of 21 students with dyslexia, who were distributed across three groups. The measurement instruments consisted of tests assessing reading accuracy, reading fluency, and visual confusion errors. The results showed that the proposed typeface outperformed the comparison conditions on reading performance indicators, achieving a mean accuracy of 90.84%, along with a clear reduction in visual confusion errors compared with the other two groups. By contrast, the modified-spacing group recorded the lowest level of performance, with a mean accuracy of 62.63%. These findings indicate that improving reading in Arabic cannot be achieved through increased spacing alone, but rather through a more consistent and distinctive internal letter design. The study concludes that the design of Arabic typefaces for individuals with dyslexia should be grounded in precise visual-cognitive analysis, and that the developed tool and the resulting typeface provide a preliminary model that may inform the development of educational materials and digital platforms in ways that enhance reading clarity and visual equity for this group.
Enhancing Clarity: Developing Arabic Typeface for People with Dyslexia
Number of pages199
Keywords: Dyslexia; Arabic digital typography; reading clarity; reading performance; letter engineering; ArabicLexia.